Transitions of the children with disabilities from the early intervention services in the regular schools - Karovska Ristovska, Aleksandra; Jachova, Zora (Faculty of Philosophy, Skopje, 2006)
Early children intervention as it is defined by Schonkoff and Meisels is consisted by a “multidisciplinary service for developmentally disabled children or incompetent children from their birth until the age of three and their families” (Meisels & Shonkoff, 1990). Early intervention as a support service for the children born with a high risk factor, and for the children with different type and degree of disability is perceived, organized and conducted differently in different countries. The conceptualization, design and implementation of the early intervention processes is dependent on the state structures (of course by the one relevant for the early intervention process), the degree of the development of the community members conciseness, the status of the health protection system, the financial power of the state etc. but the manner in which the early intervention is conducted primarily depends on the law regulations, that regulates the obligations and services that are offered by the institutions in which the early intervention is conducted. On the other hand there are law regulations for the legal rights of the users of the early intervention. The early intervention models differ in different countries, but there are differences in there positioning and functioning of the centers in a single country.
Keywords: early intervention, children with developmental disabilities